The Effect of ROM Exercise on Pain Intensity in Osteoarthritis Patients at RSU Sundari Medan - Ariga, Fajar Amanah; Sari, Youlanda; Sari, Hijrah Purnama (Jurnal Keperawatan Priority, 2025)
Osteoarthritis sufferers generally experience pain in the joint area, pain that occurs continuously can reduce the quality of life of osteoarthritis sufferers. This study aims to determine the effect of ROM exercises on the intensity of knee joint pain with osteoarthritis at RSU Sundari. The design of this study used quasi-experimental with the one group pre post test design approach. The sampling technique in this study used Probability Sampling with the Simple Random Sampling approach and obtained 26 respondents at RSU Sundari Medan. The instrument used is a sheet SOP Range of Motion, stopwatch and NRS (Numeric Rating Scale) observation sheet. Data were analyzed using the Wilcoxon Statistical Test with significance (ρ ≤ 0.05). The results of the study showed that the average pain scale before ROM was 3.00, and the average pain scale after ROM intervention for 6 days decreased to 1.00. The results of the study show that there is influence exercise ROM vs. intensity of knee joint pain with osteoarthritis at RSU Sundari (ρ value = 0.000) with a mean ranks of 10.50 and a sum of ranks of 210.00. ROM exercises can affect the intensity of the knee joint pain scale with osteoarthritis. This is because by practicing ROM, the joints will move actively, thus affecting the blood vessel system in the extremities. That the nutrition and fluids in the joints and bones are sufficient and pain due to disease will be reduced.